PENINGKATAN PEMAHAMAN MASYARAKAT DESA KURIPAN KIDUL KECAMATAN KESUGIHAN KABUPATEN CILACAP TENTANG METODE PENGURANGAN RESIDU PESTISIDA PADA KONSUMSI SAYUR DAN BUAH - Ayu Pramita; Rosita Dwityaningsih; Eka Dyah Puspita Sari (Journal of Science and Social Development, 2019)
Most of the people in Kuripan Kidul village, which is located in the southern part of Cilacap, work as farmers. The crops are mainly vegetables and fruit. The crops are sold directly to the markets near the village. The crops are regarded satisfactory in amount, but in the next year, the crops are decreasing due to pest in the land. One of the easiest and quickest way to solve the problem is by applying pesticide onto the land. Since the people are lack of information on the type, characteristic, and effect of pesticide, the residue of the pesticide is still in the crops, especially in fruit and vegetables. To help the people deal with the problem, the writers conducted counseling in forms of presentation and demonstration on the characteristic and effect of the pesticide through community service program (PKM). Some aspects that are put into priority in this program are comprehension acpect on the residue dose procedure information (maximum limit) of pesticide regarding the Indonesian National Standard (SNI) 7313:2008 and method in reducing residue of the pesticide in food material, especially in fruit and vegetables. Low level of education level causes lack of information on the appropriate use of pesticide dose in fruit and vegetables. Moreover, the people do not completely aware on the effect of pesticide use on the crops, especially fruit and vegetables, before they are consumed. One thing that still puts the writers into concern is the residue of the pesticide is still on the fruit and vegetables, so the writers focus on all people in the village, especially housewives that play important role in organizing and processing food material (fruit and vegetables) before it is consumed. Some solutions of the problem come up. One of them is by giving counseling through detailed presentation on the residue dose procedure (maximum limit) of the pesticide on the crops that is in line with Indonesian National Standard (SNI) 7313:2008 and by doing demonstration on the method in reducing residue of the pesticide in fruit and vegetables by utilizing salt solution. Salt solution is made by mixing baking soda, vinegar (apple cider vinegar), turmeric water, or salt. The counseling aims to educate people, especially housewives, to know and understand healthy way before consuming fruit and vegetables, and to support government program to make better and healthier Indonesians.